2018
DOI: 10.1371/journal.pone.0204727
|View full text |Cite
|
Sign up to set email alerts
|

Ept7, a quantitative trait locus that controls estrogen-induced pituitary lactotroph hyperplasia in rat, is orthologous to a locus in humans that has been associated with numerous cancer types and common diseases

Abstract: Pituitary adenoma is a common intracranial neoplasm that is observed in approximately 10% of unselected individuals at autopsy. Prolactin-producing adenomas, i.e., prolactinomas, comprise approximately 50% of all pituitary adenomas and represent the most common class of pituitary tumor. Multiple observations suggest that estrogens may contribute to development of prolactinoma; however, direct evidence for a causal role of estrogens in prolactinoma etiology is lacking. Rat models of estrogen-induced prolactinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…An extensive number of studies in concerning fields have confirmed that there are many pathological factors involved in the occurrence and growth of invasive pituitary adenomas. However, the exact mechanism remains to be elucidated by further studies in order to treat invasive pituitary adenomas at the molecular level [ 10 ].…”
Section: Related Workmentioning
confidence: 99%
“…An extensive number of studies in concerning fields have confirmed that there are many pathological factors involved in the occurrence and growth of invasive pituitary adenomas. However, the exact mechanism remains to be elucidated by further studies in order to treat invasive pituitary adenomas at the molecular level [ 10 ].…”
Section: Related Workmentioning
confidence: 99%
“…The interstrain variation in PRL cell responsiveness to estrogens has also been examined in genetic studies. Genetic variants that reside within Ept7 (estrogen-induced pituitary tumor, a quantitative trait locus mapped to rat chromosome 7 that is orthologous to an interval within the 8q24.21 region of the human genome, associated with risk of numerous cancer types and other common diseases) have been implicated in lactotropic cell responsiveness to estrogens [90]. In particular, Ept7 locus carries Myc, a well-known proto-oncogene, and estrogens enhance Myc expression in the rat anterior pituitary gland [46] (Figure 1).…”
Section: Effects Of Estradiol On the Cellular Microenvironment In Thementioning
confidence: 99%